Analisis Upaya Pengendalian dan Penilaian Risiko Kecelakaan Kerja dengan Metode Job Safety Analysis (JSA) pada WTM 16 di PT XYZ - Akmal Maulana Ramadhan; Kusnadi Kusnadi; Asep Erik Nugraha (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
PT XYZ is a leading company in steel pipe production in Indonesia, experiencing a severity level of work accidents reaching 239.5 in 2019, according to an analysis from observations and interviews with the HSE team. The most common accidents occur due to being hit by iron fragments, causing vision impairment and noise during the production process, resulting in hearing impairment. The Job Safety Analysis (JSA) method is used to analyze potential hazards in the pipe production process at PT XYZ. Risk assessment of work accidents is conducted using a risk assessment method, which found that in producing pipes at PT XYZ on the wang tong machine (WTM) line 16, there is 1 potential minor/tolerable work accident, 2 categorized as moderate, and 4 potential serious work accidents that need immediate prevention proposals. The recommended improvements related to work accident risks include the need for strict supervision of the use of personal protective equipment (PPE) on the WTM 16 line, increased use of PPE for work safety for all workers, especially in areas prone to work accidents, and providing rewards to workers who are deemed to have excellent implementation of occupational safety and health (OSH) during work. This reward system will also increase workers' awareness of OSH. Keywords: JSA, Occupational Hazards, Risk Analysis, Safety